Transparent microcrystalline glass and preparation method thereof
By utilizing high alumina silicate solid waste and controlling the size of calcium fluoride crystal phase, transparent microcrystalline glass with low cost and excellent performance was prepared, solving the problems of high preparation costs and waste of resources in the existing technology, and achieving efficient utilization Industrial solid waste resources.
Patent Information
- Application Number
- CN202411437959.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the production cost of transparent microcrystalline glass is high and the failure to effectively utilize industrial solid waste resources, resulting in high production costs and waste of resources.
Using high alumina silicate solid waste as raw material, transparent microcrystalline glass is prepared by grinding, acid leaching and purification and high temperature melting, and controlling the size and component ratio of the calcium fluoride crystal phase to generate nano-scale calcium fluoride crystals. Improve transparency and performance.
It realizes the preparation of transparent microcrystalline glass with low cost and excellent performance, reduces production costs, and effectively utilizes industrial solid waste resources, improving the light transmittance, mechanical strength and chemical stability of the glass.
Smart Images

Figure CN119285237A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of glass products, and in particular relates to a microcrystalline glass and a preparation method thereof. Background Art
[0002] Glass-ceramics is a type of multiphase solid material that contains both microcrystalline and glass phases, and has both the basic properties of glass and the crystal properties of ceramics. It exhibits excellent performance in mechanical properties, hardness, wear resistance, water absorption, chemical stability, and thermal stability. Through composition design, glass-ceramics can obtain materials with special functions, such as optical, electrical, magnetic, thermal, and biological functions, and are therefore widely used in various fields.
[0003] Transparent glass-ceramics is an important discovery in the development of glass-ceramics materials. Due to its good light transmittance, it is widely used in fields such as telescopes, solar cells, and optical devices. The preparation methods of transparent glass-ceramics include melting method, sintering method, sol-gel method, etc. However, these methods all require the use of high-purity raw materials, which leads to high costs, and the high melting temperature of glass leads to high production costs. Therefore, how to prepare transparent glass-ceramics with good performance and low cost has become an important topic in the field of materials.
[0004] On the other hand, copper and nickel smelting produces a large amount of industrial solid waste every year, which is rich in SiO2 and Al2O3. At present, the high-aluminum silicate solid waste is mainly simply piled up or landfilled, which occupies a large amount of land resources. If the silicon and aluminum resources in the solid waste can be effectively utilized to prepare transparent microcrystalline glass, it will not only help reduce the preparation cost of transparent microcrystalline glass, but also be conducive to the bulk consumption of solid waste resources, which will effectively promote the development of related industries. At present, there is a lack of relevant technical means in the existing technology. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a transparent microcrystalline glass with low cost and excellent performance and a preparation method thereof.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0007] A transparent microcrystalline glass, whose raw materials include the following components by mass percentage: SiO2: 29-40%; Al2O3: 20-30%; CaO: 5-15%; MgO: 1-10%; CaF2: 10-30%; Na2O: 0-5%, and a clarifier: 0-1%. The main crystal phase of the transparent microcrystalline glass is calcium fluoride, the crystallinity of calcium fluoride is 70-80%, and the size of the calcium fluoride crystal phase is 15-41nm.
[0008] In the present invention, the main crystal phase of the transparent microcrystalline glass is calcium fluoride, and the size of the calcium fluoride crystal phase is 15-41nm. The generation of the nano-sized crystal phase can improve the light transmittance of the transparent microcrystalline glass. The calcium fluoride crystal itself exhibits transparency. When the size of the crystal is much smaller than the wavelength of visible light and is at the nanometer level, the transparent microcrystalline glass exhibits high transparency.
[0009] In the above transparent glass-ceramics, preferably, the mass ratio of CaF2 to MgO is (1-5): 1. More preferably, the mass ratio of CaF2 to MgO is (2.5-5):1.
[0010] In the above transparent glass-ceramics, preferably, the mass ratio of the total mass of CaO+CaF2 to MgO is (2.5-7): 1. More preferably, the mass ratio of the total mass of CaO+CaF2 to MgO is (4-7): 1.
[0011] In order to obtain the crystalline phase structure of the above-mentioned size structure, the present invention needs to limit the ratio of CaF2 / MgO, and also limit the ratio of (CaO+CaF2) / MgO. Suitable CaF2 / MgO can obtain ideal crystals after crystallization, so that the microcrystalline glass presents transparency. Suitable (CaO+CaF2) / MgO can provide good crystallization sites, and the grains can be evenly distributed in the glass matrix. Suitable (CaO+CaF2) / MgO increases more nucleus sites during the crystallization process, and more calcium fluoride crystals can be generated. And suitable CaF2 / MgO can reduce the crystallization rate of the crystal during the crystallization process so that the growth of calcium fluoride nuclei can be controlled, reduce the crystal size, and thus promote the generation of nanocrystals. The limitation of the above two ratios can make transparent microcrystalline glass generate more nano calcium fluoride crystals.
[0012] In the above transparent microcrystalline glass, preferably, the mass ratio of SiO2 and Al2O3 is (1-1.6):1, the mass ratio of the total mass of SiO2+Al2O3 to MgO is (4.5-18):1, and the mass ratio of MgO and Na2O is (1-10):1. Suitable SiO2 / Al2O3 can make the raw materials have a suitable melting temperature so that the glass is clarified and homogenized. Suitable (SiO2+Al2O3) / MgO can make the glass have a suitable hardening rate and better glass forming performance. Suitable MgO / Na2O can make the glass have suitable viscosity and chemical stability.
[0013] In the above-mentioned transparent microcrystalline glass, preferably, part of its raw materials come from high-aluminum silicate solid waste, and the components of the high-aluminum silicate solid waste include, in terms of oxides: SiO2: 50-60%; Al2O3: 20-35%; CaO: 3-9%; MgO: 0-1%; Na2O+K2O: 0-1%; Fe2O3: 0-1%; others: 0-3%; in the raw materials of the transparent microcrystalline glass, the proportion of high-aluminum silicate solid waste is 10-50% by mass.
[0014] As a general technical concept, the present invention also provides a method for preparing the above-mentioned transparent microcrystalline glass, comprising the following steps:
[0015] (1) grinding high alumina silicate solid waste to prepare powder with a particle size of 1-50 μm;
[0016] (2) placing the ground high-aluminum silicate solid waste obtained in step (1) in an acid leaching solution, heating and stirring, and performing purification treatment, and washing the acid-leached high-aluminum silicate solid waste with deionized water until it is neutral, thereby obtaining pretreated high-aluminum silicate solid waste; this step can remove impurities in the high-aluminum silicate solid waste, such as iron oxides, which is conducive to obtaining transparent microcrystalline glass;
[0017] (3) The pretreated high-aluminum silicate solid waste obtained in step (2) and other chemical raw materials of transparent microcrystalline glass are mixed according to the designed components, ground without a medium for 10 minutes, and after being evenly mixed, they are melted at high temperature, homogenized, clarified, and then cast or calendered to obtain basic glass;
[0018] (4) The base glass obtained in step (3) is annealed and subjected to a two-step crystallization heat treatment method to obtain a transparent microcrystalline glass based on high-alumina silicate solid waste.
[0019] In the above preparation method, preferably, the acid leaching solution is one or more of HCl, H2SO4 and HNO3, and when heated and stirred, the heating temperature is 50-70°C, the stirring speed is 150-180rpm, and the purification time is 0.5-3h.
[0020] In the above preparation method, preferably, in step (3), the high temperature melting temperature is 1500-1600° C., and the time is 1-3 h;
[0021] In the step (4), the annealing temperature is 500-600°C and the annealing time is 1-5h; in the two-step crystallization heat treatment, the first temperature is 600-700°C and the holding time at the first temperature is 0.5-8h, and the second temperature is 700-900°C and the holding time at the second temperature is 0.5-5h.
[0022] The preparation method of the present invention firstly needs to pre-treat the high-aluminum silicate solid waste to remove impurity elements and prevent the impurity elements from being mixed into the raw materials of the transparent microcrystalline glass and affecting the transparency.
[0023] The following is an explanation of the role of each component:
[0024] SiO2: SiO2 is an important glass-forming oxide, which forms an irregular continuous network with the structural element of silicon-oxygen tetrahedron [SiO4], becoming the skeleton of glass. SiO2 can reduce the thermal expansion coefficient of glass, and improve the thermal stability, chemical stability, heat resistance, hardness, mechanical strength, viscosity and ultraviolet transparency of glass. However, when the content is high, a higher melting temperature is required, and crystallization may occur.
[0025] Al2O3: Al2O3 is one of the essential components of basic glass and is an intermediate oxide. It exists in glass as a tetraligand [AlO4] and an octaligand [AlO6]. 3+ A higher coordination number (6) makes oxygen tend to be closely arranged, which is conducive to adjusting into regularly arranged crystals. Al2O3 can reduce the crystallization tendency of glass, improve the chemical stability, thermal stability, mechanical strength, hardness and refractive index of glass, reduce the erosion of refractory materials, and help the opacification of fluorides. Al2O3 can control or inhibit the phase separation and crystallization of glass. It is a refractory oxide that can increase the viscosity of glass and make it more difficult to clarify and homogenize the glass. Therefore, the Al2O3 content in the base glass should not exceed 30wt%.
[0026] CaO: CaO can react with acidic oxides in the glass (such as SiO2, Al2O3) to form amorphous calcium silicate (CaSiO3), which reduces the content of oxides such as SiO2 in the glass, thereby reducing the solubility of the glass. CaO can also form stable compounds with other elements in the glass, making the glass more stable, with higher heat resistance and durability. CaO can lower the melting point of the glass and promote the fluidity of the glass. However, the content of calcium oxide needs to be controlled within a certain range. Too high a content will cause the glass to become more brittle and easy to break. Therefore, in practical applications, the CaO content needs to be controlled below 15wt% to achieve the best glass performance.
[0027] Na2O: Na2O is an oxide outside the glass network. Sodium ions (Na +) resides in the holes of the glass structure network. Na2O can increase the free oxygen to increase the O / Si ratio in the glass structure and cause bond breaking, thereby reducing the viscosity of the glass and making it easier to melt. It is a good flux for glass. Na2O increases the thermal expansion coefficient of the glass and reduces the thermal stability, chemical stability and mechanical strength of the glass. Using Na2O in the components of microcrystalline glass can reduce the crystallization activation energy and crystallization temperature of the glass, weakening the crystallization ability of the glass and increasing the residual glass phase. Therefore, Na2O cannot be introduced too much, generally not more than 5wt%.
[0028] CaF2: CaF2 is a good nucleating agent. It exists in the high-temperature melt in an ionic state and has great fluidity. During the cooling process of the melt, fluorine ions are precipitated, providing a good crystallization site for the nucleation of crystals. During the precipitation process of fluoride nanoparticles, the changes in the components and structures around them make the grains evenly distributed in the glass matrix, thus avoiding agglomeration. However, excessive CaF2 content will cause the microcrystalline glass to become opaque. Therefore, the CaF2 content should not be too high, generally not exceeding 30%.
[0029] MgO: MgO is a network-external oxide that slows down the hardening rate of glass and improves the forming properties of glass. MgO can also reduce the crystallization tendency and crystallization rate, increase the high temperature viscosity of glass, and improve the chemical stability and mechanical strength of glass. However, if the MgO content is too high, it may cause a decrease in devitrification resistance, and undesirable crystals will be obtained after crystallization, resulting in a decrease in the performance of transparent microcrystalline glass. Therefore, the MgO content does not exceed 10wt%.
[0030] In addition to the above oxides, the transparent microcrystalline glass product of the present invention also contains a clarifier, the content of which is 0-1wt%, and the clarifier is one or more of Sb2O3, SnO2, and CeO2.
[0031] PbO is a toxic substance and does not meet environmental protection requirements, so the present invention preferably does not contain PbO.
[0032] The present invention uses high-aluminum silicate solid waste as the main raw material, utilizes the aluminum oxide and silicon oxide contained in the high-aluminum silicate solid waste, effectively utilizes solid waste and resources, reduces production costs, and then coordinates chemical raw materials to regulate key components. The obtained microcrystalline glass is transparent, and its acid and alkali resistance weight loss rate is as low as less than 0.5%, and the chemical stability is excellent. The high-value utilization of high-aluminum silicate solid waste can be achieved, and the preparation method is simple, which is conducive to industrial utilization.
[0033] Compared with the prior art, the advantages of the present invention are:
[0034] The transparent microcrystalline glass and the preparation method thereof of the present invention are a kind of transparent microcrystalline glass and the preparation method thereof based on high-aluminum silicate solid waste, which fully utilizes the composition characteristics of high-aluminum silicate solid waste, and cleverly realizes the high-value utilization of industrial solid waste and the preparation of high-performance nanocrystalline transparent microcrystalline glass materials through the formulation design of solid waste and pure chemical raw materials, thus providing a new way for the resource utilization of industrial solid waste, having very important value, and greatly reducing the production cost of transparent microcrystalline glass.
[0035] The transparent microcrystalline glass obtained by the present invention has a small-sized nanocrystalline phase, and the product has the characteristics of excellent light transmittance, excellent thermal shock resistance, acid and alkali resistance, high mechanical strength, excellent chemical stability and high density. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 The present invention is a process flow chart of the method for preparing the transparent microcrystalline glass.
[0038] Figure 2 This is a macroscopic photograph of the transparent microcrystalline glass prepared in Example 1.
[0039] Figure 3 XRD diagrams of the base glass ((a) in the figure) and the transparent microcrystalline glass ((b) in the figure) prepared in Example 1.
[0040] Figure 4 This is the SEM image of the transparent microcrystalline glass prepared in Example 1. DETAILED DESCRIPTION
[0041] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0042] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The raw materials used in the embodiments of the present invention are high-aluminum silicate solid waste and purchased mineral raw materials and chemical raw materials, and trace amounts of inevitable impurities are allowed.
[0044] Embodiment 1:
[0045] A transparent microcrystalline glass based on high-aluminum silicate solid waste, wherein the raw materials include the following components by mass percentage: SiO2: 29.5%; Al2O3: 20%; CaO: 15%; MgO: 10%; CaF2: 20%; Na2O: 5%, and clarifier: 0.5%. Among them, SiO2 / Al2O3 is 1.48, (SiO2+Al2O3) / MgO is 4.95, MgO / Na2O is 2, CaF2 / MgO is 2, and (CaO+CaF2) / MgO is 3.5. The specific components are shown in Table 1.
[0046] The raw materials of the above-mentioned transparent microcrystalline glass are partly derived from pre-treated high-aluminum silicate solid waste. By mass percentage, the high-aluminum silicate solid waste accounts for 20%. The components of the high-aluminum silicate solid waste, calculated in terms of oxides, include: SiO2: 58.08%; Al2O3: 30.22%; CaO: 7.25%; MgO: 0.65%; Na2O+K2O: 0.85%; Fe2O3: 0.78%; and others: 2.17%.
[0047] like Figure 1 As shown, the method for preparing transparent microcrystalline glass based on high-aluminum silicate solid waste in this embodiment comprises the following steps:
[0048] (1) grinding high alumina silicate solid waste to prepare powder with a particle size of 1-50 μm;
[0049] (2) In order to remove impurities in the high-aluminum silicate solid waste, the high-aluminum silicate solid waste was placed in an HCl acid leaching solution, the heating temperature was 50° C., the stirring speed was 150 rpm, and the purification time was 0.5 h. The high-aluminum silicate solid waste after acid leaching was washed with deionized water until it was neutral;
[0050] (3) The purified high-aluminum silicate solid waste and chemical raw materials are mixed in the above ratio, weighed and mixed evenly, the batch is melted at 1500° C. and kept warm for 1 hour, and glass liquid is obtained after high-temperature homogenization and clarification, and the glass liquid is formed by a casting method to obtain basic glass;
[0051] (4) The obtained basic glass was annealed at 500°C for 4 hours, maintained at a first temperature of 630°C for 2 hours, and then heated to a second temperature of 700°C and maintained for 0.5 hours to obtain a transparent microcrystalline glass based on high-aluminum silicate solid waste. It was then cut, ground and polished for subsequent performance testing.
[0052] The transparent microcrystalline glass based on high alumina silicate solid waste prepared in this embodiment was tested, and the results are shown in Table 2. The crystal phase is calcium fluoride, the bending strength is 103 MPa, and the Vickers hardness is 700 kgf / mm 2 , compressive strength is 1128MPa, transmittance is 97%, acid resistance (20wt% sulfuric acid) is 99.88%, alkali resistance (20wt% sodium hydroxide) is 99.95%, the crystal phase is CaF2 (only CaF2 crystal phase), the crystallinity is 80%, and its average size is 20nm.
[0053] The actual macroscopic picture of the transparent microcrystalline glass prepared in this embodiment is as follows: Figure 2 As shown in the figure, it can be seen that the glass has high transparency. The XRD patterns of the base glass and transparent microcrystalline glass prepared in this embodiment are shown in Figure 3 As shown, the SEM image of the transparent microcrystalline glass prepared in this embodiment is as follows Figure 4 As shown by Figure 3 , Figure 4 It can be seen that there is a clear difference between the CaF2 crystal phase of the base glass and the transparent microcrystalline glass. The transparent microcrystalline glass contains CaF2 crystal phases with a size of 20nm. From the SEM, it can be seen that the nanoscale CaF2 crystal phase is dispersed throughout the glass, and the grain size observed in the SEM may be larger than predicted by the XRD analysis. This difference occurs because the large particles seen in the SEM image are actually composed of many aggregated crystals rather than a single particle.
[0054] Embodiment 2-10:
[0055] The raw material components of the transparent microcrystalline glass based on high-aluminum silicate solid waste in Examples 2-10 are shown in Table 1 below, and part of the raw materials come from the same high-aluminum silicate solid waste as in Example 1. The preparation method in each example is the same as that in Example 1.
[0056] Comparative Examples 1-2, 4-5:
[0057] The raw material components of the transparent microcrystalline glass based on high-aluminum silicate solid waste in Comparative Examples 1-2 are shown in Table 1 below, and part of the raw materials come from the same high-aluminum silicate solid waste as in Example 1. The preparation methods in each comparative example are the same as in Example 1.
[0058] Comparative Example 3:
[0059] The raw materials of Comparative Example 3 are the same as those of Example 1, and part of the raw materials of the transparent microcrystalline glass come from high-aluminum silicate solid waste that has not been pretreated. In terms of mass percentage, the high-aluminum silicate solid waste accounts for 20%, and the components of the high-aluminum silicate solid waste, calculated as oxides, include: SiO2: 58.08%; Al2O3: 30.22%; CaO: 7.25%; MgO: 0.65%; Na2O+K2O: 0.85%; Fe2O3: 0.78%; and others: 2.17%.
[0060] The method for preparing transparent microcrystalline glass based on high-aluminum silicate solid waste of this comparative example comprises the following steps:
[0061] (1) grinding high alumina silicate solid waste to prepare powder with a particle size of 1-50 μm;
[0062] (2) mixing the ground high-aluminum silicate solid waste and chemical raw materials according to the above ratio, weighing and mixing them evenly, melting the batch materials at 1500° C. and keeping the temperature for 1 hour, obtaining glass liquid after high-temperature homogenization and clarification, and obtaining basic glass after the glass liquid is formed by a casting method;
[0063] (3) The obtained basic glass was annealed at 500°C for 4 hours, maintained at a first temperature of 630°C for 2 hours, and then heated to a second temperature of 700°C and maintained for 0.5 hours to obtain a transparent microcrystalline glass based on high-aluminum silicate solid waste. It was then cut, ground and polished for subsequent performance testing.
[0064] Table 1: Raw material composition in Examples 1-10 and Comparative Examples 1-5
[0065]
[0066] The transparent glass-ceramics obtained in Examples 1-10 and Comparative Examples 1-5 were tested for performance using the following test method:
[0067] Flexural strength: Flexural strength is tested according to GB / T 37781-2019 method.
[0068] Vickers hardness: The hardness of the deeper surface layer of the microcrystalline glass sample is tested using a Vickers hardness tester. The load used in the test is 1N, maintained for 10 seconds, and each sample is tested at 3 different locations, and the average value is calculated.
[0069] Compressive strength: The compressive strength is tested according to the GB / T 50081-2019 method. The glass is placed on a press and the pressure is gradually increased until the glass breaks.
[0070] Acid resistance: Before the test, clean the glass-ceramic sample with deionized water and anhydrous ethanol, dry it in a 100℃ dryer for 30 minutes, and weigh the mass of the glass-ceramic sample after drying. Immerse the glass-ceramic sample in a 20wt% sulfuric acid solution at 25℃ for 24 hours. After the test, clean the sample with deionized water and anhydrous ethanol, and dry it in a 100℃ dryer for 30 minutes. Weigh the mass of the glass-ceramic after completion.
[0071] Alkali resistance: Before the test, clean the glass-ceramic sample with deionized water and anhydrous ethanol, dry it in a dryer at 100℃ for 30 minutes, and weigh the mass of the glass-ceramic sample after drying. Immerse the glass-ceramic sample in a 20wt% sodium hydroxide solution at 25℃ for 24 hours. After the test, clean the sample with deionized water and anhydrous ethanol, and dry it in a dryer at 100℃ for 30 minutes.
[0072] After completion, weigh the mass of the glass-ceramics.
[0073] Visible light transmittance: The transparent glass-ceramics was cut into pieces with a thickness of 0.5 mm and polished, and the transmittance at 550 nm was measured using a spectrophotometer.
[0074] Grain size: The transparent glass-ceramics is surface treated with HF acid, and the grain size is measured using a scanning electron microscope (SEM).
[0075] Crystal phase: X-ray diffraction was used to analyze the physical phase and structure of the glass-ceramics. A Cu rake was used with an operating voltage of 40 kV, a scanning speed of 5° / min, and a scanning angle of 5-80°.
[0076] The test results are shown in Table 2 below:
[0077] Table 2: Performance test results in Examples 1-10 and Comparative Examples 1-5
[0078]
[0079]
[0080] It can be seen from Table 2 that in the above embodiments, the amount of calcium fluoride crystals generated and the crystal size can be adjusted by controlling the mass ratios of CaF2 / MgO and (CaO+CaF2) / MgO. When the limitations in the present invention are not met, the content of calcium fluoride crystals generated is very small, and the amount of calcium fluoride crystals precipitated is low, resulting in lower performance.
[0081] The transparent microcrystalline glass prepared in Examples 1-10 was compared with the standard microcrystalline glass for construction, and the results are shown in Table 3 below.
[0082] Table 3: Performance comparison table
[0083]
[0084] It can be seen from Table 3 that the microcrystalline glass prepared in the embodiment of the present invention is superior to the traditional microcrystalline glass for construction in terms of transparency, mechanical properties, and acid and alkali resistance.
Claims
1. A transparent microcrystalline glass, characterized in that: The raw materials include the following components by mass percentage: SiO2: 29-40%; Al2O3: 20-30%; CaO: 5-15%; MgO: 1-10%; CaF2: 10-30%; Na2O: 0-5%, and clarifier: 0-1%. The main crystalline phase of the transparent microcrystalline glass is calcium fluoride, the crystallinity of calcium fluoride is 70-80%, and the size of the calcium fluoride crystal phase is 15-41nm.
2. The transparent microcrystalline glass according to claim 1, characterized in that: The mass ratio of CaF2 and MgO is (1-5):
1.
3. The transparent microcrystalline glass according to claim 2, characterized in that: The mass ratio of CaF2 and MgO is (2.5-5):
1.
4. The transparent microcrystalline glass according to claim 1, characterized in that: The mass ratio of the total mass of CaO+CaF2 to MgO is (2.5-7):
1.
5. The transparent microcrystalline glass according to claim 4, characterized in that: The mass ratio of the total mass of CaO+CaF2 to MgO is (4-7):
1.
6. The transparent microcrystalline glass according to claim 1, characterized in that: The mass ratio of SiO2 and Al2O3 is (1-1.6):1, the mass ratio of the total mass of SiO2+Al2O3 to MgO is (4.5-18):1, and the mass ratio of MgO and Na2O is (1-10):
1.
7. The transparent microcrystalline glass according to any one of claims 1 to 6, characterized in that: Part of its raw materials comes from high-aluminum silicate solid waste, and the components of the high-aluminum silicate solid waste, calculated as oxides, include: SiO2: 50-60%; Al2O3: 20-35%; CaO: 3-9%; MgO: 0-1%; Na2O and K2O: 0-1%; Fe2O3: 0-1%; others: 0-8%; in the raw materials of the transparent microcrystalline glass, the high-aluminum silicate solid waste accounts for 10-50% by mass.
8. A method for preparing the transparent microcrystalline glass according to claim 7, characterized in that: The following steps are involved: (1) Grinding high alumina silicate solid waste; (2) placing the ground high-aluminum silicate solid waste obtained in step (1) in an acid leaching solution, heating and stirring, and performing purification treatment, and washing the high-aluminum silicate solid waste after acid leaching with deionized water until it is neutral, thereby obtaining pretreated high-aluminum silicate solid waste; (3) The pretreated high-aluminum silicate solid waste obtained in step (2) and other chemical raw materials of transparent microcrystalline glass are mixed according to the designed components, and then melted, homogenized, clarified, and then cast or rolled to obtain basic glass; (4) The base glass obtained in step (3) is annealed and subjected to a two-step crystallization heat treatment method to obtain a transparent microcrystalline glass based on high-alumina silicate solid waste.
9. The preparation method according to claim 8, characterized in that: The acid leaching solution is one or more of HCl, H2SO4 and HNO3. When heated and stirred, the heating temperature is 50-70°C, the stirring speed is 150-180rpm, and the purification time is 0.5-3h.
10. The preparation method according to claim 8, characterized in that: In the step (3), the high temperature melting temperature is 1500-1600° C. and the time is 1-3 hours; In the step (4), the annealing temperature is 500-600°C and the annealing time is 1-5h; in the two-step crystallization heat treatment, the first temperature is 600-700°C and the holding time at the first temperature is 0.5-8h, and the second temperature is 700-900°C and the holding time at the second temperature is 0.5-5h.
Citation Information
Patent Citations
Glass-ceramic and production method thereof
CN109704583A
Transparent oxyfluorosilicate microcrystal glass for high-temperature observation window and preparation method of transparent oxyfluorosilicate microcrystal glass
CN110240412A
High-fracture-toughness microcrystalline glass for mobile phone backboard and preparation method of high-fracture-toughness microcrystalline glass
CN112851122A
High-alumina microcrystalline glass containing high-volume coal gangue and preparation method of high-alumina microcrystalline glass
CN114368914A